2021
DOI: 10.1186/s12864-021-07878-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of formin gene family highlights candidate genes related to pollen cytoskeleton and male fertility in wheat (Triticum aestivum L.)

Abstract: Background Formin, a highly conserved multi-domain protein, interacts with microfilaments and microtubules. Although specifically expressed formin genes in anthers are potentially significant in research on male sterility and hybrid wheat breeding, similar reports in wheat, especially in thermo-sensitive genic male sterile (TGMS) wheat, remain elusive. Results Herein, we systematically characterized the formin genes in TGMS wheat line BS366 named T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In our previous study, we found that TaGH9s were involved in pollen fertility conversion [ 31 ]. To investigate the roles of the TaGH9 family on anther and pollen development in BS366, pollen and anther morphology at critical stages of pollen development stage were observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we found that TaGH9s were involved in pollen fertility conversion [ 31 ]. To investigate the roles of the TaGH9 family on anther and pollen development in BS366, pollen and anther morphology at critical stages of pollen development stage were observed.…”
Section: Resultsmentioning
confidence: 99%
“…L). In our previous study, it was found that GH9 may be involved in male sterility by RNA-seq [ 31 ]. GH9 had differential alternative splicing between fertile and sterile condition, involved in fertility conversion.…”
Section: Discussionmentioning
confidence: 99%
“…However, a comprehensive study on the identification of putative formin-related genes in the soybean remains missing. Therefore, a genome-wide investigation of formin-encoded genes was conducted by referring to the existing public soybean genome database [ 18 , 19 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genomic resources generated from other plants could be used to identify the potential genes involved in the sexual differentiation and flower development of P. amurense . A literature survey was undertaken to list 1281 genes involved in sex differentiation and flower development in other plants, involving 189 papers from more than 30 journals (the latest published in 2022) [ 4 , 8 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , ...…”
Section: Methodsmentioning
confidence: 99%